Conformational Heterogeneity of Cyclosporin A in Cyclophilin 18 Binding - Lin, Weilin (PLoS One, 2016)
The immunosuppressive drug cyclosporin A (CsA) binds to its receptor protein cyclophilin 18 (Cyp18) in two distinct kinetic phases, while the mechanism remains elusive. Stopped-flow measurements coupled with titration and competition experiments were used to investigate the puzzling two-phase process of CsA and Cyp18 interaction. This study leads to the dissection of different conformational fractions of either direct fast binding or slow binding with rate-limiting conformational inter-conversion and the real-time measurement of k(on) value (8.34 ± 0.22 x10(6) M(-1)s(-1)) in solution. Furthermore, our study indicates that the structure of CsA during dissociation from the protein possesses a distribution of conformations different from those in solution under equilibrium condition.